THE LEVEL OF DEPRESSION AMONG PARENTS OF AUTISM CHILDREN: A QUANTITATIVE STUDY - Ikeu Nurhidayah; Nisa Lailatun Noor Ambya; Fanny Adistie; Nur Oktavia Hidayati (Jurnal Ilmu Keperawatan dan Kebidanan, 2022)
ABSTRACTBackground: Caring for a child with autism in the family is a long-term challenge for the parents that impact physical and psychological health. Negative psychological problems that occur continuously will result in depression to the parents.Objective: The purpose of this study is to determine the level of depression in parents who have children with autism at four schools of special needs children (SLB Risantya, SLB Autis Prananda, SLB Jatis Hurip, and SLB D YPAC at Great Bandung Region.Methods: This study used a quantitative descriptive design with a cross-sectional approach. The sampling method used was total sampling, and 39 respondents were obtained. The instrument used was Beck Depression Inventory-II (BDI-II) standard instrument in the Indonesian version.Result: This study showed that 76,9% of parents who have children with autism had minimal depression/normal, 12,8%  of mild depression,  7,7% of moderate depression, and 2,6% of severe depression.Conclusion: The Conclusions of this study indicate that many parents who have children with autism were at minimal/normal depression. However, there were still 2.6% of respondents in severe depression. Nurses needed to provide nursing care that focuses on families, such as counselling and sustainably doing depression screening to parents who have children with autism.